Modeling the Socio-Cultural Drivers of Adaptation Strategy Choice: Evidence from Smallholder Farmers in Berbere District, Oromia, Ethiopia - Kena, Terefe Melkamu; Amenu, Geremew Huluka (Geosfera Indonesia, 2026)
Climate change is a significant threat to agricultural productivity, particularly in underdeveloped countries where rain-fed farming is common. Without adaptation, climate change may negatively impact agricultural productivity; however, adopting adaptive measures can reduce vulnerability and potentially increase some of the benefits of climate change. This study explores the sociocultural factors that influence farmers in Oromia's Berbere district to select particular adaptation strategies. We gathered information from 339 randomly chosen smallholder vegetable growers. We used a multinomial logit model to examine the variables affecting their selection of adaptation measures. The findings showed that the adoption of vegetable diversification strategies was significantly influenced by factors like family structure, the transmission of indigenous knowledge, land tenure and cultural ties, access to credit, communal trust systems, cultural perceptions of climate change, and farming experience. The dissemination of indigenous knowledge, adoption of technology, cultural acceptance, financial availability, community trust, and non-farm revenue were also important elements that favorably impacted the selection of varietal adaptation strategies in the region. The decision to modify planting dates in response to climate change was also greatly influenced by elements such as indigenous knowledge transfer, land tenure and cultural attachment, technology adoption, cultural interpretation of climate change, and farming experience. The adoption of spatial risk distribution as a climate change adaptation strategy was found to be negatively impacted by the distance to agriculture, whereas family structure, land tenure, and cultural connection emerged as significant positive characteristics in this location. In order to adapt to climate change, irrigation methods are greatly influenced by a number of factors, including family dynamics, the speed at which we adopt new technology, cultural attitudes, understanding of climate change, and income from nonfarm sources. This emphasizes how important it is for legislators to incorporate these components into household-level climate adaptation plans.